2022
DOI: 10.3389/fpsyg.2022.855179
|View full text |Cite
|
Sign up to set email alerts
|

Sport Participation in Early and Middle Adolescence: The Interplay Between Self-Perception and Psychobiosocial Experiences in Predicting Burnout Symptoms

Abstract: Adolescence is characterized by pubertal physical changes, cognitive development, and modified social expectations. Adolescent athletes often enter a more challenging stage of athletic development associated with increased specialization, and become vulnerable to feelings of burnout. It is therefore important to consider intrapersonal psychological factors that can improve sport participation experiences and prevent burnout. Accordingly, the aim of the current study was to examine the interplay between self-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…To support this model, researchers in the sports science discipline found that stressors such as high sporting demands, a lack of recovery, and high expectations from coaches all contributed to the development of burnout in Swedish elite athletes (Johanssan et al, 2008). Other researchers found that academic demands, social relationships, overtraining, and performance based self esteem all contributed to high levels of burnout in collegiate athletes (Morano et al, 2022). Thus, this model emphasizes that athlete burnout is a complex interaction between a variety of factors.…”
Section: Multidimensional Perspectivementioning
confidence: 87%
“…To support this model, researchers in the sports science discipline found that stressors such as high sporting demands, a lack of recovery, and high expectations from coaches all contributed to the development of burnout in Swedish elite athletes (Johanssan et al, 2008). Other researchers found that academic demands, social relationships, overtraining, and performance based self esteem all contributed to high levels of burnout in collegiate athletes (Morano et al, 2022). Thus, this model emphasizes that athlete burnout is a complex interaction between a variety of factors.…”
Section: Multidimensional Perspectivementioning
confidence: 87%
“…This approach often violates adolescents’ self-perception, making them feel as if they are fulfilling others’ expectations rather than pursuing their own interests ( Barber and Harmon, 2002 ). Moreover, a controlling parenting style may cultivate a maladaptive focus on outcomes rather than the learning process ( Aunola et al, 2000 ; Hibbard and Walton, 2014 ), which could hinder skill development and enjoyment in sports ( Mallinson-Howard et al, 2019 ; Morano et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Developing a healthy sense of self-worth is an ongoing process that thrives on the accumulation of minor triumphs along the way. This boost in confidence is not merely a byproduct of sports; it acts as a catalyst for further growth [ 39 ]. The cultivation of admirable qualities is intrinsically linked to a healthy sense of self-worth, serving as a foundation upon which other aspects of a person's personality can be built.…”
Section: Literature Reviewmentioning
confidence: 99%